Young Individuals Are More Stable and Stand More Upright When Using Rollator Assistance During Standing up and Sitting Down - Krafft, F. C.; Herzog, M.; Stein, T.; Sloot, L. H. (Frontiers in Bioengineering and Biotechnology, 2022)
Four-wheeled walkers or rollators are often used to assist older individuals in maintaining an independent life, by compensating for muscle weakness and reduced movement stability. However, limited biomechanical studies were performed to understand how rollator support affects posture and stability, especially when standing up and sitting down. Therefore, this study examined how stability and posture change with varying levels of rollator support and on an unstable floor. The aim was to collect comprehensive baseline data during standing up and sitting down in young participants. Twenty able-bodied, young participants stood up and sat down, both (1) unassisted and using a custom-made robot rollator simulator under (2) full support, and (3) touch support. Unassisted and assisted performance were analyzed on normal and on an unstable floor using balance-pads with a compliant surface under each foot. Using 3D motion capturing and two ground-embedded force plates, we compared assistive support and floor conditions for movement duration, the relative timing of seat-off, the movement stability (Center of pressure (COP) path length and sway area), and for posture after standing up (lower body sagittal joint angles) using ANOVA analysis. The relative event of seat-off was earliest under full support compared to touch and unassisted conditions under normal but not under unstable floor conditions. Duration of standing up and sitting down did not differ between the support conditions on normal nor unstable floors. COP path length and sway area during both standing up and sitting down were lowest under full support regardless of both floor conditions. Hip and knee joints were least flexed under full support, with no differences between touch and unassisted in both floor conditions. Hence, full rollator support led to increased movement stability, while not slowing down the movement, during both standing up and sitting down. During standing up, the full support led to an earlier seat-off and a more upright standing posture when reaching a stable stance. These results indicate that rollator support when handles are correctly aligned does not lead to the detrimental movement alterations of increased forward-leaning. Future research will verify in older persons with stability and muscle weakness deficiencies.